Development of 64Cu Automatic Separation Apparatus - LI Guang;ZHAO Ziyu;WEN Kai;CHU Haomiao;LI Chao;DUAN Fei;MA Chengwei;WANG Chengzhi;WANG Xiaoming;WANG Chunlin;LI Hongyu (Yuanzineng kexue jishu, 2023)
In recent years, 64Cu has received extensive attention along with its growing application in nuclear medicine positron emission tomography (PET) diagnosis. A 64Cu automatic separation apparatus adapted to the Cyclone-30 cyclotron was developed to realize the process automation from target dissolution to nuclide separation and purification for stable 64Cu production at large scale. The apparatus consists of a tank for target dissolution and a system for separation and purification. The operation interface, programming language and specific programming instructions were determined by programming design. Based on the established separation and purification process of 64Cu, the apparatus was designed followed by assembling and testing. After the process parameters of the apparatus were confirmed through a series of conditional experiments, the hot verification experiments at small-scale and three batches of mass production process verification were carried out consecutively, showing that this self-developed apparatus has steady function and can realize distant control. The whole separation process could be finished in 3 h. The radiochemical recovery of 64Cu (after calibration) is greater than 90%, which meets the expected goal of the design. The 64Cu product was tested with over 95% of radiochemical purity, higher than 99.9% of radio nuclidic purity. The contents of impurities such as iron, copper and zinc were less than 1.5 μg/GBq, while cobalt, gold and nickel were less than 0.5 μg/GBq, which meets the requirements of group standard and can be used for preparation of 64Cu radiopharmaceuticals. In conclusion, this self-developed apparatus has low cost and independent intellectual property rights, and its performance and the product quality of 64Cu are comparable to other competitive foreign products. Compared with the manual separation process, the automatic one has significant advantages in terms of the stability of product quality, the process controllability, the time-consuming and the radiation protection of operators. At present, the apparatus has already been used in 64Cu production routinely.